Molecular and Phylogenetic Characterization of Non-O157 Shiga Toxin-Producing Escherichia coli Strains in China - Bai, Xiangning; Hu, Bin; Xu, Yanmei; Sun, Hui; Zhao, Ailan; Ba, Pengbin; Fu, Shanshan; Fan, Ruyue; Jin, Yujuan; Wang, Hong; Guo, Qiusheng; Xu, Xuebin; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Shiga toxin-producing Escherichia coli (STEC) causes diarrhea and hemorrhagic colitis with life-threatening complications, such as hemolytic uremic syndrome. The aim of this study was to assess the molecular epidemiologic features of non-O157 STEC strains from different resources in China and illustrate the role of animal reservoirs or animal-derived foodstuffs in human STEC infections. A collection of 301 non-O157 STEC isolates from domestic and wild animals (i.e., cattle, goat, pig, yak, pika, and antelope), raw meats (i.e., beef, pork, mutton, chicken, and duck), diarrheal patients, and healthy carriers in different regions of China were selected in this study. Of the 301 analyzed STEC isolates, 67 serogroups and 118 serotypes were identified; this included some predominant serogroups associated with human disease, such as O26, O45, O103, O111 and O121. Eighteen different combinations of stx subtypes were found. Eleven isolates carried the intimin gene eae, 93 isolates contained ehxA, and 73 isolates carried astA. The prevalence of other putative adhesion genes saa, paa, efa1 and toxB was 28.90% (87), 6.98% (21), 2.31% (7), and 1% (3), respectively. The phylogenetic distribution of isolates was analyzed by multilocus sequence typing (MLST). Ninety-four sequence types were assigned across the 301 isolates. A subset of isolates recovered from yak and pika residing in the similar wild environments, Qinghai-Tibetan plateau, showed similar genetic profiles and more tendencies to cluster together. Isolates from goat and mutton exhibited close genetic relatedness with those from human-derived isolates, providing evidence that transmission may have occurred locally within intraspecies or interspecies, and importantly, from animal reservoirs or raw meats to humans. Comparing isolates in this study with highly virulent strains by MLST, along with serotyping and virulence profiles, it is conceivable that some of isolates from goat, yak, or raw meats may have potential to cause human diseases.